Spinning micropipette liquid emulsion generator for single cell whole genome amplification. Issue 23 (24th October 2016) - Chen, Zitian; Fu, Yusi; Zhang, Fangli; Liu, Lu; Zhang, Naiqing; Zhou, Dong; Yang, Junrui; Pang, Yuhong; Huang, Yanyi
Abstract : The spinning micro-pipette liquid emulsion (SiMPLE) generator can produce highly stable monodisperse picoliter-size water-in-oil emulsions which can be integrated with conventional experimental operations. Abstract : Many on-chip approaches that use flow-focusing to pinch the continuous aqueous phase into droplets have become the most popular methods that provide monodisperse emulsion droplets. However, not every lab can easily adapt a microfluidic workflow into their familiar protocols. We develop an off-chip approach, spinning micro-pipette liquid emulsion (SiMPLE) generator, to produce highly stable monodisperse water-in-oil emulsions using a moving micropipette to disperse the aqueous phase in an oil-filled microcentrifuge tube. This method provides a simple way to produce picoliter-size droplets in situ with no dead volume during emulsification. With SiMPLE, single-cell emulsion whole genome amplification was performed to demonstrate that this novel method can seamlessly be integrated with experimental operations and supplies that most researchers are familiar with. The SiMPLE generator has effectively lowered the technical difficulties in applications relying on emulsion droplets.